2015
DOI: 10.1002/da.22376
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Depressive Symptoms: Individual Participant Meta-Analysis of 10 Cohort Studies

Abstract: Background Personality is suggested to be a major risk factor for depression but large-scale individual-participant meta-analyses on this topic are lacking. Method Data from 10 prospective community cohort studies with a total of 117 899 participants (mean age 49.0 years; 54.7% women) were pooled for individual-participant meta-analysis to determine the association between personality traits of the Five Factor Model and risk of depressive symptoms. Results In cross-sectional analysis, low extraversion (poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
249
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 354 publications
(292 citation statements)
references
References 58 publications
39
249
2
2
Order By: Relevance
“…As hypothesized, negative affectivity was associated with initial levels of PTSD symptoms and impaired mental functioning, but not to initial physical symptoms or functional impairment. Negative affectivity is akin to neuroticism by reflecting a tendency to experience negative emotions and poor coping, and the current results are in line with the previous research which identified neuroticism as a risk factor for psychiatric illness in general [10,12,28,32,61]. One mechanisms linking negative affectivity to worse PTSD and mental functioning could be heightened sensitivity to negative stimuli, such as biased processing of threat information [85][86][87][88].…”
Section: Personality Domains and Initial Health Consequences Of Traumasupporting
confidence: 80%
See 1 more Smart Citation
“…As hypothesized, negative affectivity was associated with initial levels of PTSD symptoms and impaired mental functioning, but not to initial physical symptoms or functional impairment. Negative affectivity is akin to neuroticism by reflecting a tendency to experience negative emotions and poor coping, and the current results are in line with the previous research which identified neuroticism as a risk factor for psychiatric illness in general [10,12,28,32,61]. One mechanisms linking negative affectivity to worse PTSD and mental functioning could be heightened sensitivity to negative stimuli, such as biased processing of threat information [85][86][87][88].…”
Section: Personality Domains and Initial Health Consequences Of Traumasupporting
confidence: 80%
“…Detachment showed an even more robust association with mental health outcomes as expected, and was also related to physical functioning. Akin to low extraversion, detachment is characterized by low engagement, enthusiasm and confidence, thus results are in line with previous evidence that low extraversion is a risk factor for psychiatric illness and functional impairment [10,12], possibly because it impacts social interactions, which are crucial protective factors in physical and mental health [89][90][91][92][93]. Finally, as hypothesized, psychoticism was associated with initial levels of PTSD.…”
Section: Personality Domains and Initial Health Consequences Of Traumasupporting
confidence: 75%
“…Our findings imply that this could also be the case in interventions promoting smoking cessation. In addition, as neuroticism is related to depressive symptoms (40,41) and depression is highly co-morbid with smoking (42), personality-informed interventions to reduce smoking could also support those with depressive symptoms. Further research should also investigate whether the success in current smoking cessations programs vary depending on individuals personality dispositions.…”
Section: Discussionmentioning
confidence: 99%
“…Such outcomes, in turn, may have a long-term impact on personality, such as reductions in the tendency to be self-disciplined and organized or to be exploratory and curious. Indeed, cognitive decline, greater frailty, and more depressive symptoms and disease burden have been associated with reduced conscientiousness and openness over time (Hakulinen et al, 2015; Mõttus, Johnson, Starr, & Deary, 2012; Stephan et al, 2017 ; Sutin et al, 2013; Wettstein et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, higher disease burden, biological dysfunction, depressive symptoms, and worsening cognition are related to higher neuroticism, and lower extraversion, openness, agreeableness and conscientiousness over time (Hakulinen et al, 2015; Jokela, Hakulinen, Singh-Manoux, & Kivimaki, 2014; Stephan, Sutin, Luchetti, & Terracciano, 2016; Wettstein et al, 2017). Worsening functional status, such as higher frailty over time is also related to maladaptive personality changes (Stephan, Sutin, Canada, & Terracciano, 2017).…”
Section: Introductionmentioning
confidence: 99%